Holding UNPOL to account: individual criminal accountability of United Nations police personnel - Kihara-Hunt, Ai (International humanitarian law series, 2017)
UN police in peace operations -- Evidence of the commission of crimes by UN police -- Current UN machinery for collecting information regarding alleged crimes for domestic criminal proceedings -- Criminal jurisdiction under international and national law -- Immunity as a potential legal barrier -- Is there an obligation to investigate and prosecute?